Distribution of 226Ra Radionuclide in Upwelling Event Off Ulsan, Gampo and Pohang, Korea - Muslim Muslim (Atom Indonesia, 2009)
Upwelling is an important event in the sea for it makes the area to become more productive. The objective of this study is to determine the distribution of radium-226 as radiotoxic in the upwelling area in the summer season. Measurements of the horizontal and vertical activities of 226Ra in the Ulsan, Gampo and Pohang waters were conducted in June, August 1999 and June 2000 when the upwelling event was expected to occur. Water temperature, salinity and dissolved oxygen (DO) were also measured concurrently. The thermocline layer or the layer where the temperature decreased drastically occurred at a depth between 30 m to 100 m for samples dated June 1999 and 30 m to more than 100 m for samples dated August 1999 and June 2000. The salinity decreased with depth but the DO concentration increased in this layer. The condition affected the vertical distribution of 226Ra in the study area, where the 226Ra activities showed to be relatively homogeneous vertically in each station. This indicates that the upwelling which occurred in the study area was capable to distribute the 226Ra activities from the bottom to the surface. Thus, the 226Ra distribution at that time did not increase with depth, opposite to what usually occurs in the ocean at normal condition. The 226Ra activities also did not decrease after elapsed time of one year, in fact, it increased. However, horizontally the 226Ra activities decreased with increasing distance from the coastal zone. Based on these results, it can be concluded that the upwelling event in the Ulsan, Gampo and Pohang was effective for increasing the 226Ra activities and was capable to create homogeneous 226Ra activities from the bottom to the surface in the water column, and the source of 226Ra was likely to originate from outside area (i.e. coastal zone) and bottom area.Received: 25 March 2009; Revised: 24 August 2009; Accepted: 30 September 2009